Implementation of Simultaneous Village Head Elections - Tombiling, Marcella Natalia (CV. Rayyan Dwi Bharata, 2024)
Simultaneous village head elections (PKDS) are a form of democracy implemented in Indonesia, where all villages in a region simultaneously conduct elections for village heads at the same time. This research utilizes a normative juridical approach by referring to the legislation governing PKDS. The analysis shows that the implementation of PKDS is based on the principles of democracy and village autonomy regulated by the applicable laws. Clear and precise regulations regarding the stages, procedures, and mechanisms of PKDS provide a strong foundation for the implementation of this process. However, there are several challenges including coordination among relevant institutions, public awareness, understanding, and participation in the election process, as well as fairness in the treatment of candidates and voters. This study provides recommendations including enhancing socialization and education to emphasize the importance of public participation in village head elections, improving coordination among relevant institutions, and strengthening oversight to ensure fairness and transparency in the election process. The findings of this research are expected to serve as a reference for the government and stakeholders in enhancing the effectiveness and integrity of PKDS in the future.